Effects of theta burst peripheral magnetic stimulation on cortical excitability and upper limb function after stroke: protocol for a randomized controlled trial - Lin, Xiaoying; Du, Ketao; Ding, Rongqi; Chen, Qiuyu; Niu, Xiaomin; Yang, Qinjie; Liao, Chunyang; Xin, Tiantian; Li, Shuqin; Fu, Xiaying; Cheng, Jianghua (Frontiers in Neurology, 2025)
IntroductionPost-stroke spasticity affects 25%−40% of survivors, causing pain and functional impairment. Current non-invasive treatments target either central or peripheral pathways alone. This neglects the critical imbalance between spastic agonists and antagonists. We designed this protocol to address this gap through dual-site peripheral theta-burst stimulation.MethodsThis single-center, three-arm, sham-controlled, single-blind randomized controlled trial enrolled 54 stroke survivors (aged 40–80, 3–12 months post-stroke, Modified Ashworth Scale score ≥1). Participants were randomized in a 1:1:1 ratio to receive a 10-session intervention over 2 weeks (5 days/week). Each session consisted of stimulation followed by 30 min of conventional physical therapy. The stimulation protocols were: Group 1: active iTBS over extensor carpi radialis longus + sham cTBS over flexor carpi radialis; Group 2: sham iTBS + active cTBS; Group 3: active iTBS + active cTBS. Stimulation was delivered using a MagTD stimulator at 110%−120% of the peripheral motor threshold (mean 38.4% maximum stimulator output), with 600 pulses per session (50 Hz burst frequency, 5 Hz theta rhythm).Anticipated resultsWe hypothesize that Group 3 (combined stimulation) will yield the greatest reduction in spasticity (MAS decrease ≥ 1) and the most significant improvements in upper-limb function (FMA-UE, ARAT) compared to Groups 1 and 2. These clinical gains are expected to correlate with neurophysiological changes (MEP amplitude, cortical silent period), supporting the central-peripheral synergy model.DiscussionThis protocol tests a novel dual-site pTBS paradigm. Positive findings would provide preliminary evidence for network-based rehabilitation. This could inform larger trials and potentially transform post-stroke spasticity management.